Peran Unit Pelaksana Teknis (UPT) Pelaksana Penyuluh Pertanian Bawean dalam Pemberdayaan Petani melalui Demonstrasi Plotting (DEMPLOT) Tembakau di Pulau Bawean - Umam, Khatibul; Jumadi, Rahmad; Nurdyawati, Resya (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The Bawean Island in Gresik Regency possesses significant potential in agriculture, yet it remains dominated by traditional crops like rice and maize. Recently, the Agricultural Extension Technical Implementation Unit (UPT) introduced a Demonstration Plotting (Demplot) program to promote tobacco cultivation as a new and economically promising commodity. This study aims to analyze the role of UPT in empowering farmers through the tobacco Demplot program and to identify the challenges and opportunities in introducing tobacco as a new commodity. A qualitative approach was used, incorporating field observations, in-depth interviews, documentation, and literature review. The results highlight the pivotal role of UPT in providing technical training, production inputs, and strengthening farmer groups, which led to increased skills, productivity, and income. However, challenges such as limited technical knowledge and social acceptance remain. The program's success underscores the importance of participatory and comprehensive approaches in agricultural extension. This research provides strategic recommendations for sustainable agricultural diversification in Bawean.